Sex and Secularism - Scott, Joan (The Public Square, 2017)
How secularism has been used to justify the subordination of womenJoan Wallach Scott’s acclaimed and controversial writings have been foundational for the field of gender history. With Sex and Secularism, Scott challenges one of the central claims of the “clash of civilizations” polemic—the false notion that secularism is a guarantee of gender equality.Drawing on a wealth of scholarship by second-wave feminists and historians of religion, race, and colonialism, Scott shows that the gender equality invoked today as a fundamental and enduring principle was not originally associated with the term “secularism” when it first entered the lexicon in the nineteenth century. In fact, the inequality of the sexes was fundamental to the articulation of the separation of church and state that inaugurated Western modernity. Scott points out that Western nation-states imposed a new order of women’s subordination, assigning them to a feminized familial sphere meant to complement the rational masculine realms of politics and economics. It was not until the question of Islam arose in the late twentieth century that gender equality became a primary feature of the discourse of secularism.Challenging the assertion that secularism has always been synonymous with equality between the sexes, Sex and Secularism reveals how this idea has been used to justify claims of white, Western, and Christian racial and religious superiority and has served to distract our attention from a persistent set of difficulties related to gender difference—ones shared by Western and non-Western cultures alike